2018
DOI: 10.1007/s11325-018-1703-x
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin serum levels are increased in male patients with obstructive sleep apnea

Abstract: Catestatin serum levels are significantly increased in male OSA population and positively correlate with disease severity in non-obese patients. OSA status is independently predicted by catestatin levels; however, this finding is restricted to patients with moderate-to-severe disease. Further studies are necessary to elucidate the mechanistic role of catestatin in the complex pathophysiology of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
0
17
0
4
Order By: Relevance
“…It has been previously shown that inflammatory process affects the secretion of enterochromaffine cells in the gut of IBD patients [20]. Accordingly, it seems that ChgA, a precursor of CST, is increased in colon and plasma in patients with IBD [31,44,45].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been previously shown that inflammatory process affects the secretion of enterochromaffine cells in the gut of IBD patients [20]. Accordingly, it seems that ChgA, a precursor of CST, is increased in colon and plasma in patients with IBD [31,44,45].…”
Section: Discussionmentioning
confidence: 94%
“…Catestatin (CST) is a novel multifunctional peptide proteolytically cleaved from chromogranin A (ChgA), that primarily acts as an inhibitor of catecholamine secretion in vitro in cultured cells and in vivo from mouse adrenal medulla, and as stimulator of histamine release [10][11][12]. Studies implicate its connection with multiple functions throughout various systems, including vasodilatation [13], immunoregulation [14], insulin resistance [15][16][17], antimicrobial effect [18,19] and obstructive sleep apnea [20]. Furthermore, it has been reported to be a key regulator of cardiovascular function, with cardioprotective effects including exhibiting the trough suppression of atherosclerosis [21], negative inotropic and lusitropic cardiac effects [22], inhibition of coronary vasoconstriction [21], a reduction in oxidative stress in ischemic-reperfused myocardium [22], a decrease in endothelial inflammation and regulation of blood pressure [10,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of catestatin and lipid metabolism, no comparable data are available for the HF population. In a study among untreated hypertensive patients, catestatin levels correlated positively with HDL-cholesterol levels but no associations were observed with respect to the total cholesterol or other cholesterol fractions [50], while CST correlated negatively with HDL cholesterol among obstructive sleep apnea patients [11]. Similarly, catestatin significantly retarded aortic atherosclerotic lesions with declined lipoprotein-induced foam cell formation in a preclinical experiment [51], while its levels were inversely associated with the severity of atherosclerosis, among patients with CAD [52].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, catestatin (CST) is a pleiotropic cardioprotective peptide that counterbalances the negative effects of SNS by promoting vasodilation [8] and by inhibiting catecholamine secretion [9,10]. Previous studies have demonstrated that high levels of CST might reflect increased sympathoadrenal activity [11,12,13], are associated with increased mortality in HF [14,15], and are a marker of poor ventricular remodeling after myocardial infarction (MI) [16]. Furthermore, CST levels were associated with disease severity in HF [17,18] and were similar between patients with preserved (HFpEF) and reduced (HFrEF) left ventricular ejection fraction (LVEF) phenotypes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in an adult population of hypertensive patients who were mostly obese with MS and patients with OSA who were mostly overweight or obese identified significant correlations between catestatin and HDL cholesterol levels, but interestingly reported opposing results . In addition, according to Durakoğlugil et al, triglyceride levels negatively correlate with plasma catestatin concentrations.…”
Section: Discussionmentioning
confidence: 93%